Correlation of Moraxella catarrhalis macrolide susceptibility with the ability to adhere and invade human respiratory epithelial cells. Issue 1 (31st December 2022) - Liu, Ya-li; Ding, Rui; Jia, Xin-miao; Huang, Jing-jing; Yu, Shuying; Chan, Hiu Tat; Li, Wei; Mao, Lei-li; Zhang, Li; Zhang, Xin-yao; Wu, Wei; Ni, An-ping; et al.
ABSTRACT: Recently, the prevalence of macrolide-resistant Moraxella catarrhalis has been reported, especially among Chinese children. The fitness cost of resistance is reported to render the resistant bacteria less virulent. To investigate the correlation between macrolide susceptibility of M. catarrhalis and pathogenicity, the whole genome of 70 M. catarrhalis isolates belonging to four clonal complexes with different macrolide susceptibilities was sequenced. The gene products were annotated with the Gene Ontology terms. Based on 46 extracted essential virulence genes, 19 representative isolates were selected to infect type II alveolar cells (A549 cells). The ability of these isolates to adhere and invade human epithelial cells and to produce cytokines was comparatively analysed. Furthermore, mice were infected with a pair of M. catarrhalis isolates with different pathogenic behaviours and macrolide susceptibilities to examine pulmonary clearance, histological findings, and the production of cytokines. The percentages of annotations for binding, metabolic process, cellular process, and cell were non-significantly different between the macrolide-resistant and macrolide-susceptible groups. The presence of uspA2, uspA2H, pilO, lbpB, lex1, modM, mboIA, and mboIB significantly differed among the four clonal complexes and macrolide susceptibility groups. Furthermore, compared with those in macrolide-susceptible isolates, the adhesion ability was stronger ( P = 0.0019) and the invasion ability was weaker ( P < 0.0001) in the macrolide-resistant isolates. Mouse experiments revealed that pulmonary macrophages elicit immune responses against M. catarrhalis infection by significantly upregulating the Csf2, Il4, Il13, Il1b, Il6, Tnf, and Il18. Therefore, M. catarrhalis populations exhibited diverse pathogenicity in vitro and in vivo .